Production characteristics of White Karaman, Chios x White Karaman (F1) crossbred lambs.: I.: Growth, survival ability and body measures - Esen, F; Yildiz, N (Scientific Technical Research Council Turkey, 2000)
The aim of this study was to investigate the growth, survival ability and body measurements of White Karaman and Chios x White Karaman (F-1) crossbred lambs. The data for the study were obtained from 34 White Karaman and 32 Chios x White Karaman (F-1) crossbred lambs in suckling period and from 8 White Karaman and 10 Chios x White Karaman (F-1) crossbred lambs to determine body measurements. Lambs were fed with alfalfa hay and concentrates in the suckling period. The average birth weight was 3.73 and 3.78 kg, the weaning weight was 20.23 and 19.03 kg, the daily weight gain from birth to the weaning was 157 and 145 g and the survival ability at weaning (105th day of age) was 68.96 % and 78.57 % in the purebred and crossbred lambs, respectively. Rump hight was 57.12 and 59.44 cm (P < 0.05), and pelvis width was 20.62 and 22.11 cm (P < 0.05) in purebres and crossbred lambs at the age of 6 months, respectively.
Keywords: White Karaman; Chios; crossbreeding; growth; survival ability